Stress management in the workplace for employees with hypertension: a randomized controlled trial. Issue 5 (21st March 2018) - Clemow, Lynn P; Pickering, Thomas G; Davidson, Karina W; Schwartz, Joseph E; Williams, Virginia P; Shaffer, Jonathan A; Williams, Redford B; Gerin, William
Abstract: While behavioral interventions can improve blood pressure (BP) in individuals with hypertension, getting such services to people who could benefit remains difficult. Workplace programs have potential as dissemination vehicles. The objective is to evaluate the effectiveness of a standardized stress management program delivered in groups at the workplace for reducing BP compared with enhanced usual care. This randomized controlled trial studied 92 urban medical center employees with hypertension randomized into two groups. The intervention was a 10-week group workshop on cognitive-behavioral coping skills. Enhanced usual care included self-help materials for BP reduction and physician referral. Intervention group participants' systolic BP (SBP) decreased 7.5 mm Hg over controls between baseline and follow-up, from 149.1 (95% CI: 146.0–152.1) to 140.0 (95% CI: 134.7–145.2), p < .001. The differential change between intervention and enhanced usual care groups (Group × Time interaction) was 7.5 mm Hg ( t = −2.05; p = .04). Diastolic BP reductions were not significantly different. Scores on measures of emotional exhaustion and depressive rumination showed significant improvements and correlated with reductions in SBP. There was no significant change in the usual care group. A standardized worksite group intervention produced clinically meaningful reductions in SBP in participants with hypertension. Abstract : Employees with high blood pressure who participated in a weekly stress and anger management group in the workplace reduced their systolic blood pressure more than employees who did not participate.